Patterns of bird species richness at two sampling scales in the Karoo biome of South Africa. (March 2020) - Lee, Alan Tristram Kenneth; Wright, Dale R.
Abstract: Species richness has become the common currency of studies of biodiversity. Here we consider measures of species richness for the birds of the arid Karoo region of South Africa. We measured species richness at two scales: at the broad-scale using pentads (5 × 5′); and at the fine scale, using point counts to determine important landscape features. Point counts within randomly selected pentads were conducted throughout the two biomes that comprise the Karoo (Succulent and Nama). Features at points were used to model covariates of species richness at the fine scale, while the total number of unique species from counts was used as the dependent variable at the broad scale. We considered determinants of total species richness; and the subset of ten bird species endemic to the Karoo. Finally, we modelled covariates of presence for 100 of the most common bird species. We found increasing vegetation height and decreasing sand-cover best explain total species richness, while lower Prosopis sp cover and increasing altitude explained endemic species richness at the broad scale. At the finer scale, presence of water and farmsteads were associated with highest general species richness, but with lower numbers of endemics. The presence of water, a 'green' score, sand cover and topography were identified as the most important variables explaining presence of individual species, but often with contrasting effects between species. We conclude that patterns of endemic bird species richness were explained by different variables compared to total species richness. We expect this information will inform landholders, wildlife managers and conservation practitioners in this unique arid zone environment. Highlights: Bird species richness increases with vegetation height and decreasing sand cover. Endemic richness increased with altitude and decreased with Prosopis trees. Point features with high richness include water, farmhouses, green-ness, valleys. Models of landscape-features of the 10 Karoo endemic bird species are provided. Landscape-feature influence for 101 most common species is summarised.